PEMANFAATAN MEDIA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 1 PEUSANGAN SIBLAH KRUENG KABUPATEN BIREUEN - Mizwar, Edi; Habiburrahim; Silahuddin (Indonesian Journal of Islamic and Social Science, 2024)
This research aims to determine and describe the use of media in learning Islamic Religious Education at SMP Negeri 1 Peusangan Siblah Krueng, Bireuen Regency. The approach used in this research is a qualitative approach, while the method used in this research is a descriptive research method. Data collection techniques are carried out through observation, interviews and documentation. Based on the results of research conducted, it shows that the use of learning media can increase students' understanding and arouse students' enthusiasm and interest in participating in the learning process. Furthermore, the use of learning media ensures diversity and variety of learning methods, thereby enabling students to gain a more comprehensive understanding. In implementing media-based learning activities, Islamic religious education teachers at SMP Negeri 1 Peusangan Siblah Krueng, Bireuen Regency face several obstacles such as limited resources, technical skills, training support, and creativity development. Solutions that can be taken to overcome these obstacles include improving facilities, training teachers in learning technology, and encouraging teacher creativity by using available media so that the teaching and learning process becomes more effective and interesting.